(untitled) (Marketing Journal, 2026)
Abstract This article analyzes the scientific and methodological foundations of using IT outsourcing in supporting enterprise information systems. In the context of digital transformation, ensuring the continuity, reliability, and security of information systems has become a key factor in enterprise performance. The study examines the essence ofIT outsourcing, its main forms and implementation mechanisms, and evaluates its impact on economic efficiency, technical stability, and management processes. The results indicate that a properly selected IT outsourcing model optimizes operational costs, improves service quality, and enhances the speed of managerial decisionmaking. Practical recommendations are also proposed to mitigate organizational and information security risks. Keywords: information systems, IT outsourcing, enterprise management, digital technologies, technical support, information security, service quality, economic efficiency.